Dataset of Search Results Organized as Learning Paths Recommended by Experts to Support Search as Learning - Gonzalez-Ibanez, R; Proaño-Rios, V (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In this article, we introduce a dataset of curated learning paths (LPs) to support search as learning. LPs were obtained through an online survey delivered to experts in different domains. Data were then analyzed and described in terms of a set of variables. The resulting dataset comprised 83 LPs, each containing three web pages, for an overall collection consisting of 249 documents. The dataset is intended to provide information scientists, education researchers, and industry professionals, who provide information services in educational contexts, a valuable resource to (i) investigate patterns in the order of LPs, (ii) improve ranking models and/or re-ranking methods, (iii) explain the structure of the recommended LPs, and (iv) investigate alternative approaches to display search results based on the features of LPs. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.